Fine‐needle‐aspiration cytology of a proximal type epithelioid sarcoma: A case report. Issue 10 (3rd July 2015) - Pendse, Avani A.; Dodd, Leslie G.
<x xml:space="preserve">Abstract</x> Epithelioid sarcoma is a rare mesenchymal neoplasm, with an as yet unidentified cell of origin. Two subtypes of epithelioid sarcoma, distal/classic and proximal/large cell type, are recognized in the literature; with the proximal‐type having a lower incidence amongst the two. Here, we present a case of proximal‐type epithelioid sarcoma in a previously healthy young man. Fine‐needle‐aspiration of a large axillary mass was performed for diagnosis. The cytologic findings included a dispersed population of large epithelioid to polyhedral cells with abundant cytoplasm. Immunohistochemical staining showed coexpression of keratin and vimentin, as well as loss of INI1 staining, consistent with an epithelioid sarcoma, proximal subtype. Diagn. Cytopathol. 2015;43:859–862. © 2015 Wiley Periodicals, Inc.